2004
DOI: 10.1111/j.1525-1497.2004.40153.x
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and health outcomes

Abstract: Low literacy is associated with several adverse health outcomes. Future research, using more rigorous methods, will better define these relationships and guide developers of new interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
642
5
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,664 publications
(674 citation statements)
references
References 54 publications
15
642
5
12
Order By: Relevance
“…In multivariable analyses, the association between health literacy and task performance was substantially reduced once fluid and crystallized cognitive abilities were entered into models (without cognitive abilities: β=−28.9, 95 % Confidence Interval (CI) - 31.4 T he relationship between adult literacy skills, health knowledge, behaviors, and clinical outcomes has been repeatedly investigated. [1][2][3] More than 500 research publications have demonstrated associations between crude measures of reading and numeracy skills with various healthrelated outcomes, including risk of hospitalization and mortality. [4][5][6] This has been the foundation for the field now known as 'health literacy' research.…”
Section: Objectivementioning
confidence: 99%
“…In multivariable analyses, the association between health literacy and task performance was substantially reduced once fluid and crystallized cognitive abilities were entered into models (without cognitive abilities: β=−28.9, 95 % Confidence Interval (CI) - 31.4 T he relationship between adult literacy skills, health knowledge, behaviors, and clinical outcomes has been repeatedly investigated. [1][2][3] More than 500 research publications have demonstrated associations between crude measures of reading and numeracy skills with various healthrelated outcomes, including risk of hospitalization and mortality. [4][5][6] This has been the foundation for the field now known as 'health literacy' research.…”
Section: Objectivementioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] For the purpose of our study, non-medical refers to all factors, other than a patient's clinical condition, that potentially influence admission decisions. In retrospective studies, non-medical factors associated with hospital admission include both patient-level (e.g., income, 4,5 insurance status, 6,7 homelessness, 8,9 spouse's health status, 10 health literacy 11 ) and system-level features (e.g., access to care, 12,13 provider continuity 14 ). But the role that these non-medical factors play in admission decisions is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, several other resources, such as education, word knowledge, and decision-making manner, contribute to health literacy and are connected to recollection or memory function. The research, however, did not attempt to explain the effects of health literacy on the memory function in the old age [9,12,13]. The understanding of the complicated interrelation between aging, recollection or memory function, and connected resources that contribute to health literacy is essential for developing targeted interventions, for improving the health literacy and thus, consequently, for better health and financial outcomes among the already large and fast-growing population of older adults [8].…”
Section: Pielęgniarstwo XXI Wiekumentioning
confidence: 99%